Anarchy and old dogs - Cotterill, Colin (Cotterill, Colin. Dr. Siri Paiboun series., 2007)
When a blind dentist is run over by a truck, Dr. Siri Paiboun, the reluctant national coroner of Laos, suspects that this was no traffic accident. A coded message written in invisible ink is recovered from the dentist's body, and Dr. Siri begins to follow clues that hint at deep--and dangerous--political intrigue. Dr. Siri only intended to investigate a murder; is he now being drawn into an insurrection? Will he, as a fortune teller predicts, betray his country?